If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3-2x=-3x+3(x+3)
We move all terms to the left:
-3-2x-(-3x+3(x+3))=0
We calculate terms in parentheses: -(-3x+3(x+3)), so:We add all the numbers together, and all the variables
-3x+3(x+3)
We multiply parentheses
-3x+3x+9
We add all the numbers together, and all the variables
9
Back to the equation:
-(9)
-2x-12=0
We move all terms containing x to the left, all other terms to the right
-2x=12
x=12/-2
x=-6
| -0.3m+1=-7 | | x+7=3x-43 | | 6(n+5)=78 | | 17+3k=83 | | 3=1x3 | | +2-2s=3/4s=13 | | (6x+7)^.5+3=9x | | 3=4x-17=7 | | k/6+20=40 | | 7x+10=107 | | 21–2v=3 | | 4-9x=-14+ | | 7x-3+5x=-x-3+13x | | 7+8d=47 | | m/2+35=45 | | 4x+1=9x+26 | | 3(x-5)=5x+41 | | 3t3-tt=3 | | 2x=94-8 | | 330t=93t | | 20x^2-40x-25=0 | | 2x-8(x-2)=52 | | 2/4x+5=x+4 | | 5-x=4x+3 | | 55z-9(9z+12)=-64 | | 10x+22x-5=8(4x-7) | | 4x-7=8x2 | | u4+ 7= 10 | | 9/5+5m/4=81/20 | | (7x-12)=(4x-17) | | 5(3×-2)-4=6x+2 | | 6-1/3x=1-1 |